Sexual minorities are not a homogeneous population: health disparity differences based on residence in rural versus urban settings - Ethan Morgan; Kathryn Lancaster; Yootapichai Phosri; Janelle Ricks; Christina Dyar (James Cook University, 2023)
Introduction: Past research has demonstrated that, separately, sexual minorities (SMs) and rural-dwelling populations are each at elevated risk for chronic diseases relative to heterosexuals and urban-dwelling populations, respectively. Little research, however, has assessed whether rural SM populations may experience even further chronic disease risk. Methods: Data come from the US National Survey on Drug Use and Health, 2015-2019. Survey-weighted logistic regression analyses were used to assess the relationship between sexual identity and various health-associated outcomes, stratified by rural/urban status and adjusted for demographic and other risk factors. Results: Urban bisexual and rural lesbian females had significantly decreased odds of having any health insurance and increased odds of asthma, chronic obstructive pulmonary disease, hepatitis, any heart disease, and STIs relative to their heterosexual counterparts, with disparities affecting bisexual women living in rural areas being largest. Urban gay males had increased odds of having health insurance relative to urban heterosexuals. Both urban gay and bisexual males also experienced increased odds for several chronic diseases, however, among rural residents increased risk was only observed for bisexual males with regards to high blood pressure. Conclusion: Rural-dwelling bisexual women experience elevated likelihood for physical health conditions compared to urban-dwelling bisexual women, but few other rural populations experience elevated risk. Urban gay men, meanwhile, are more likely to possess insurance but simultaneously experience worse health outcomes across several domains of diseases, suggesting lower utilization of healthcare services. Future research should strive to avoid pooling all SMs into a single risk group as we have clearly demonstrated that strong differences exist based on both sex and rural/urban status.